Asia-Latin America free trade agreements: An instrument for inter-regional liberalization and integration - Ganeshan Wignaraja; Dorothea Ramizo; Luca Burmeister (Asian Development Bank Institute (ADBI), 2012)
Trade integration and free trade agreement (FTA)-led cooperation between Asia and Latin America has increased since the early 2000s. Using new criteria, this paper examines whether Asia-Latin America FTAs have facilitated market-led integration by liberalizing trade and behind the border regulatory barriers. Overall Asia-Latin America FTAs provide the foundations for inter-regional integration by liberalizing goods and services trade as well as some regulatory barriers. Future FTAs can support deeper integration by reducing residual regulatory barriers. Other policy priorities include forming a large inter-regional FTA, stimulating business use of FTAs and accelerating structural reforms.
Keywords: F15; O24; O53; O54; 330; asia; latin america; free trade agreements; inter-regional liberalization; trade integration; market-led integration; Freihandelszone; Handelsliberalisierung; Handelshemmnisse; Asien; Lateinamerika